Association of gender in patients with extractions of endodontically treated teeth - SANGGAYA, DHINESH KUMAR; PRABU, DINESH; RAMANATHAN, VISALAKSHI (The journal of contemporary issues in business and government, 2020)
The key to successful endodontic treatment is to thoroughly debride the canal system of infected or necrotic pulp tissue and microorganisms, and to completely seal the canal space, thus preventing the persistence of infection and/or reinfection of the pulp cavity.The aim of this study is to provide clinical data on the prevalence of endodontically treated tooth extractions. 8547 patients visiting Saveetha Dental College were used as the samples in this study to assess the extraction of its endodontically treated tooth or non endodontically treated tooth with ethical permission and approval for the project. Collected data was tabulated in Excel and statistical analysis was performed using Chi-square test. The results show that endodontically treated tooth extraction is 70% while non endodontically treated tooth extractions is 30% with male predominance. There is no association seen with gender and extractions of endodontically treated tooth tooth extraction statistically.